FACTORS AFFECTING THE MOTIVATION OF THE COLLEGE OF NURSING FACULTY MEMBERS ON RESEARCH PRODUCTION, PRESENTATION AND PUBLICATION - Lopez, Marcelo; Villarante, Carmen; Sanchez, Marc; Micabalo, Kingie; Inventor, Arniel (AGPE THE ROYAL GONDWANA RESEARCH JOURNAL OF HISTORY, SCIENCE, ECONOMIC, POLITICAL AND SOCIAL SCIENCE, 2023)
With the desire for efficiency and effectiveness in the academe profession producing research outputs, universities must highlight faculty members' motivation towards research-related efforts. The study aims to identify the elements influencing the college of nursing faculty members' motivation for research production, presentation, and publication. The descriptive quantitative research design was used for the investigation using a snowball sampling technique for data collection. The study identified probationary, regular, and part-time faculty members in the College of Nursing. Simple frequency and percentage, and weighted mean were used to treat the collected data. This study showed that the teacher's access to a source of income, university-sponsored research tutorials, seminars, and workshops, and the attraction of organizational grant and reward systems are essential in motivating the teacher. The findings further revealed that peer influence and organizational support systems are vital motivating factors to boost teachers' self-confidence in research presentations and publications. The study concluded that the extensiveness of faculty motivation's elements resides in improving their incentive to generate, present, and publish research articles. The study further concludes that faculty desire to produce, present, and publish research outputs are influenced and affected by elements including but not limited to financial considerations, administrative assistance, peer influence, and organizational support.